2006
DOI: 10.4049/jimmunol.176.4.2114
|View full text |Cite
|
Sign up to set email alerts
|

IL-3-Mediated TNF Production Is Necessary for Mast Cell Development

Abstract: Mouse mast cell development and survival are largely controlled by the cytokines IL-3 and stem cell factor (SCF). We have found that IL-3 stimulation of bone marrow cells induces the production of TNF via a PI3K- and MAPK kinase/ERK-dependent pathway. Specifically, Mac-1-positive cells were responsible for TNF production, which peaked on days 7–10 of culture and decreased rapidly thereafter. The importance of IL-3-induced TNF secretion was demonstrated by the failure of TNF-deficient bone marrow cells to survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 56 publications
4
18
0
Order By: Relevance
“…S3 B and C). As previously described (14), gene deficiency of TNF-α reduced the proliferation and c-kit high FcεRI high population of bone marrow cells (TNF-α −/− and H-PGDS −/− TNF-α −/− ), that were rescued by a supplement with 1 ng/mL TNF-α. Thus, PGD 2 does not influence IL-3-mediated mast cell growth and differentiation in vitro, but TNF-α is required for it to occur.…”
Section: H-pgds Deficiency Enhances Proangiogenic Properties In Tumorssupporting
confidence: 55%
See 1 more Smart Citation
“…S3 B and C). As previously described (14), gene deficiency of TNF-α reduced the proliferation and c-kit high FcεRI high population of bone marrow cells (TNF-α −/− and H-PGDS −/− TNF-α −/− ), that were rescued by a supplement with 1 ng/mL TNF-α. Thus, PGD 2 does not influence IL-3-mediated mast cell growth and differentiation in vitro, but TNF-α is required for it to occur.…”
Section: H-pgds Deficiency Enhances Proangiogenic Properties In Tumorssupporting
confidence: 55%
“…In response to LLC growth, H-PGDS-deficient mast cells produce TNF-α excessively. This response is suppressed by the administration of a synthetic PGD 2 receptor agonist or a degradation product of PGD 2 , 15-deoxy-Δ 12,14 -PGJ 2 . Additional TNF-α deficiency partially counteracts the tumorigenic properties seen in H-PGDS-deficient mast cells.…”
mentioning
confidence: 99%
“…Mac1 ϩ macrophages may be acting as feeder cells during the early time points of MC culture. 14 We attempted mixing experiments to determine whether the growth defect was intrinsic to the MCs or other cells types present early in culture. MC cultures did not develop when ATF3-null MCs were plated onto adherent WT feeder cells.…”
Section: Atf3 Is Required For In Vitro MC Maturationmentioning
confidence: 99%
“…9). It has been suggested that TNF␣ supports MC differentiation (21). To test this, we performed MCp assays with MNCs derived from the diseased intestines of APC ⌬468 mice, in the presence or absence of exogenous TNF␣.…”
Section: Adenoma-associated Mastocytosismentioning
confidence: 99%